Occurrence and Distribution of Microplastics on the Beaches of Limón on the Southern Caribbean Coast of Costa Rica - Emanuelle Assunção Loureiro Madureira; André Luiz Carvalho da Silva; Gustavo Barrantes-Castillo; Fábio Vieira de Araújo (Micro)
This study aimed to characterize the temporal and spatial occurrence of microplastics on the beaches of the Caribbean coast of Limón, Costa Rica. The selected beaches comprise a stretch of 70 km, characterized by large environmental protection areas, agricultural and residential areas with low occupation density, urban areas, and port areas. Despite the great importance of the beaches for the country, studies related to solid waste pollution remain scarce on the Caribbean coast. The methodology consisted of conducting fieldwork in 2017 and 2019 to collect materials on five beaches and laboratory analyses for extraction using hypersaline solution and the quantification and characterization of microplastics based on type, size, and color. The results show that the beaches studied in the northwestern sector had the highest concentrations of microplastics, with emphasis on Cieneguita Beach and Airport Beach, with a predominance of pellets (56.7%) followed by fragments (21.8%). These beaches are inserted in a coastal stretch with a strong concentration of industrial, port, and airport activities. The lower occurrence of microplastics in the southeastern sector (Manzanillo and Gandoca) may be related to the greater number of preservation areas. With varying sizes, shapes, and colors, most microplastics had a worn appearance, which suggests reworking by coastal processes and subsequent deposition on the studied beaches. The impact of this type of pollution on the coast of Limón is notorious and shows the need for further research into the occurrence and distribution of microplastics on Caribbean beaches so that possible sources and damage to coastal ecosystems can be identified.